(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
This article presents a critical review of three prominent modern methods: Communicative Language Teaching (CLT), Task-Based Learning (TBL), and Technology-Enhanced Language Learning (TELL). We examine the theoretical foundations of each method, analyzing their strengths and weaknesses in terms of promoting language proficiency, fostering student engagement, and developing intercultural competence. The discussion includes practical examples of classroom activities and strategies for effective implementation. Furthermore, we address common challenges associated with each method and propose solutions for overcoming them. The article concludes by advocating for a flexible and adaptive approach that integrates elements of all three methods to create a dynamic and effective learning environment. Finally, we identify areas for future research that could further enhance the effectiveness of foreign language teaching."